PERAN GENERASI MUDA DALAM ERA NEW NORMAL - Nanggala, Agil (UNIVERSITAS SLAMET RIYADI, 2020)
The young generation has a vital role in bringing the Indonesian nation to the peak of its civilization. Basically this research aims to provide an academic footing for the younger generation regarding the urgency of new normal policies, as well as the proposed efforts made. This study uses a qualitative approach to the method of studying literature, the process of data analysis in this study are: data reduction, data display, verification and conclusion drawing. The research results obtained, namely: the younger generation in the success of the new normal policy can be in groups or communities, as well as individually or personally, as well as technical activities can be directly or online.Keywords: New Normal, Young Generation, Pandemic Covid-19ABSTRAKGenerasi muda memiliki peran vital dalam membawa bangsa Indonesia menuju puncak peradabannya. Pada dasarnya penelitian ini bertujuan untuk memberikan pijakan akademik bagi generasi muda mengenai urgensi kebijakan new normal, serta usulan upaya yang dilakukan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, proses analisis data dalam penelitian ini adalah: reduksi data, display data, verifikasi serta penarikan kesimpulan. Hasil penelitian yang didapatkan, yaitu: generasi muda dalam menyukseskan kebijakan new normal bisa secara kelompok atau komitas, maupun secara individu atau personal, serta teknis kegitannya bisa secara langsung maupun online.Kata Kunci : New Normal, Generasi Muda, Pandemi Covid-19